Seroprevalence survey of Chlamydophila abortus infection in breeding goats on commercial farms in the Otavi Veterinary District, northern Namibia - Alaster Samkange (Onderstepoort Journal of Veterinary Research, 2010)
A total of 1 076 sera from breeding goats were randomly collected from 24 different farms and tested with CHEKIT®-ELISA (IDEXX Laboratories B.V., 1 119 NE Schiphol-Rijk, Nederland) for antibodies against Chlamydophila abortus. The farms were divided into two categories of twelve farms each,based on their previous history of observed abortions over the previous 12 months: those with low (< 5%) levels of abortion and those with high (≥ 5%) levels of abortion. The farmers were also interviewed on their level of awareness about chlamydophilosis, its zoonotic importance and vaccination measures against the disease. The study detected overall seroprevalence levels of 25% for the farms and 8% for the individual animals (at 95% confidence). A total of six out of twentyfour farms (25%) had at least one positive breeding animal. Only five out of the twenty-four (20.8%)farmers interviewed were aware of chlamydophilosis and its zoonotic dangers. None of the 24 farmers interviewed practised any vaccination against chlamydophilosis. There was a significantly higher number of seropositive animals from farms with high levels of abortion, compared to those animals from farms with low levels of abortion (p = 0.0001). This study underscores the need for a higher level of farmer awareness and training on chlamydophilosis and its zoonotic dangers.